Kejahatan Berbasis Identitas Digital: Menggagas Kebijakan Kriminal untuk Dunia Metaverse - Zul Khaidir Kadir (Jurnal Litigasi Amsir, 2025)
This study examines the challenges of criminal policies related to digital identity in the metaverse using a qualitative method with a conceptual approach. Digital identity, which includes personal information, digital assets, and user interaction patterns, is the main foundation of an individual’s existence in the metaverse however, the lack of specific regulations indicates weaknesses in current criminal policies. The results of the study show that the metaverse presents new crime risks that have not been fully accommodated by the existing legal system, such as identity theft, avatar counterfeiting, and digital asset fraud. To overcome this, fundamental reforms of criminal policy are needed that include a cross-border collaborative approach, strengthening the regulation of technology platforms, and developing appropriate legal standards. The success of these policies relies heavily on collaboration between governments, technology companies, and civil society.